An exploration in pitfalls in interpreting SDHB immunohistochemistry. Issue 2 (27th May 2022) - Ding, Chien‐Kuang Cornelia; Chan, Salina; Mak, Julie; Umetsu, Sarah E; Simko, Jeffry P; Ruiz‐Cordero, Roberto; Saunders, Tara; Chan, Emily
Abstract : Aims: Mutations and epimutations in genes encoding the succinate dehydrogenase complex ( SDHx ) are associated with multiple tumour types in which identification of SDH‐deficiency has significant management implications. Immunohistochemistry (IHC) for the succinate dehydrogenase B (SDHB) subunit can help to detect SDH‐deficiency, which manifests as complete loss of staining in tumour cells. However, a subset of SDH‐deficient tumours can show aberrant cytoplasmic SDHB‐IHC staining patterns and be misinterpreted as 'retained', a diagnostic pitfall complicating interpretation. Herein, we characterise in detail aberrant SDHB‐IHC staining patterns in SDH‐deficient tumours. Methods and results: We identified 23 tumours from patients with known germline SDHx and/or molecularly confirmed SDHx pathogenic/likely‐pathogenic variants in their tumour. Of these, eight (35%) showed significant SDHB‐IHC staining: one SDHA‐, one SDHB‐, three SDHC‐ and three SDHD ‐mutated cases. In all eight cases, closer inspection revealed differences in intensity and intracellular distribution of SDHB‐IHC staining in tumour cells compared to adjacent non‐neoplastic cells: non‐neoplastic cells showed intense cytoplasmic coarse granular staining; tumour cells in seven of eight cases showed weak to focally strong, cytoplasmic blush to fine granular staining, in > 80% of cells. The remaining case in the initial block showed variably strong non‐granular cytoplasmic staining with globular perinuclear accentuation throughout, only subtly distinct from the staining pattern of non‐neoplastic cells. SDHB‐IHC performed on two additional blocks in this latter case revealed significant intratumoral heterogeneity, including convincing areas of complete loss. Conclusions: When evaluating SDHB‐IHC, care should be taken to distinguish true retained expression from aberrant cytoplasmic expression, which may be difficult to appreciate. Sometimes this may require additional molecular testing.